Social-Cultural Barriers of Muslim Women Athletes: Case Study of Professional Female Athletes in Iran - Shohreh Sadeghi; Seyed Nasrollah Sajjadi; Hosein Rajabi Nooshabadi; Majid Jalali Farahani (Journal of Management Practices, Humanities and Social Sciences, 2018)
The purpose of this research is to identify socio-cultural barriers of Muslim women athletes. A case study on professional female athletes in Iran is carried out in the current study to highlight the barriers that women athletes have to go through in their careers. Qualitative research was performed based on grounded theory. To collect data, the semi-structured interviews were used. The sample was taken from professors of sports management in universities of Iran who were active in the main body of the sport, as well as the chairman and vice chairman of the federations that were selected purpose-fully. The results of the eleven semi-structured interviews found five categories, namely personal problems, social beliefs, government thought, cultural attitudes, legal-law and customary barriers, all of which included the central issue of social cultural barriers. On the basis of these findings some useful recommendations for policy makers are made which might help them to develop an inclusive and encouraging environment for the athletes and eventually the athletes will be able to overcome the social and cultural hurdles in their career path.